Case report of unusual cause of trigeminal neuralgia: Trigeminal neuralgia secondary to enlarged suprameatal tubercle. (June 2021) - Ibrahim, Bilal; Muhsen, Baha'eddin A.; Najera, Edinson; Borghei-Razavi, Hamid; Adada, Badih
Abstract: Background: Classic trigeminal neuralgia (TN) is caused by vessels compressing the trigeminal nerve root entry zone. The cause is usually impingement of the superior cerebellar artery, anterior inferior cerebellar artery, or a vein. Other rare causes have been reported including aneurysmal compression, skull base tumors, and vascular malformations. An enlarged suprameatal tubercle (EST) as a cause of TN has not yet been described. Case presentation: We report the first case of 37 year old female patient presented with severe TN involving the three branches of trigeminal nerve who failed medical treatment and underwent multiple balloon compression for left TN with minimal improvement. The severity of pain was assessed using Barrow Neurological Institute (BNI) pain intensity score. Patient had brain MRI with CISS sequence and CT scan for the brain. After careful revision of her imaging studies, patient found to have prominent and heavily calcified left supra meatal tubercle. Her preoperative BNI score was 5. Patient had left retrosigmoid craniotomy and drilling of left suprameatal tubercle. No other structures were seen in contact with left trigeminal nerve root entry zone. Patient had significant improvement on her pain, postoperative BNI score was 1 until the last follow-up 4 years. Conclusion: EST is a rare cause of TGN and should be suspected as the offending compressing structure when no other causes seen on imaging studies. Highlights: Enlarged suprameatal tubercle as a rare cause of trigeminal neuralgia. Trigeminal neuralgia due to bony compression have to be ruled out in obscured cases. Drilling of suprameatal tubercle to decompress trigeminal nerve root entry zone.